If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2q = 2 Solving 8 + -2q = 2 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -2q = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -2q = 2 + -8 -2q = 2 + -8 Combine like terms: 2 + -8 = -6 -2q = -6 Divide each side by '-2'. q = 3 Simplifying q = 3
| 0.5x+7=58 | | 3x+5=7(x+3) | | 3x+5=7(x+5) | | 7=3u-2 | | 12x-9=4x+13 | | 2(n^2+n-17)=0 | | 4x+-5=2x+3 | | 5x(2-6)=4xy | | 84=6n+5(n+8) | | 5(x+4)+x=2x+3(x+12) | | .6x=165000000 | | 2(x+y+1)=4y | | (3x-1)(2X^2+4x+3)= | | x+(x*.15)=7.2 | | x+(x*.15)=8 | | x+(x*.15)=6.6 | | -11+p=-8(7p-6)-2 | | x+(x*.15)=7.3 | | 3w+2=8 | | 8x-3=8x-21 | | 136=8(3b-4) | | 25x=5x+100 | | 6+7lnx=15.8 | | -7x+30=10x-4 | | x-7=-13+3x | | 7-3q=-11 | | 4x+5x=10-x | | 10=6+2j | | 3x+112=5x+100 | | f(2)=13 | | -5d^2-22d+8=0 | | 6(x+4)-4x-15= |